Decision Support System for Determining Website-Based Fruit Quality in Pagar Alam Fruit Farmers Group - Muslim, Buhori; Arif, Alfis (SENATIK STT Adisutjipto, 2019)
Fruit is a healthy supplement, the biggest consumer of fruit is found in big cities. Pagar Alam is an area that produces various types of fruit. Assessment of fruit quality by farmer groups, still using manual methods so that it has some weaknesses. Weakness in evaluating the quality of fruit manually causes an inaccurate assessment because the assessment system is done by estimating the quality of a sample of fruits based on the experience of quality assessors and not based on standardized aspects of assessment. For this reason, a Decision Support System (SPK) was developed to determine the quality of fruit based on a website that helps assessors of the quality of fruits in farmer groups in determining accurate fruit quality with a quick process. This system uses PHP as its programming language, the method used by RAD is an object oriented approach. The system can be used to support fruit quality assessment decisions, thus providing data on the quality of current fruit yields and can be used as a reference for farmers to improve the quality of fruit production in the next harvest.